Impact of the FLEGT license on Indonesian plywood competitiveness in the European Union - Prasada, Imade Yoga; Nugroho, Agus Dwi; Lakner, Zoltan (Elsevier, 2022)
Indonesia is the only country with the FLEGT (Forest Law Enforcement, Governance, and Trade) license that allows them to sell plywood in the EU market. However, an assessment of the impact of FLEGT on Indonesian plywood competitiveness has not yet been made. This study aims to determine the impact of the FLEGT license on Indonesian plywood competitiveness in the EU market. The study was conducted using secondary data from January 1999 to July 2021. RCA, two-stage least squares, and Propensity Score Matching were used to analyse the data. The result shows that the FLEGT license has deceased Indonesian plywood competitiveness in the EU market. However, this condition is still better than implementing the Voluntary Partnership Agreements phase. Indonesian plywood competitiveness has also reduced due to the increase in the consumer price index and the Indonesian plywood price. Therefore, we recommend strengthening the promotion of Indonesian plywood in EU countries, educating Indonesian plywood stakeholders about the FLEGT system, and managing the inflation rate.